2014
DOI: 10.1371/journal.pone.0105020
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Heterozygosity-Survival Correlations in a Wild Songbird Population: Contrasting Effects between Juvenile and Adult Stages

Abstract: The relationship between genetic diversity and fitness, a major issue in evolutionary and conservation biology, is expected to be stronger in traits affected by many loci and those directly influencing fitness. Here we explore the influence of heterozygosity measured at 15 neutral markers on individual survival, one of the most important parameters determining individual fitness. We followed individual survival up to recruitment and during subsequent adult life of 863 fledgling pied flycatchers born in two con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 69 publications
0
19
1
Order By: Relevance
“…Nevertheless, no such evidence has been found in the few attempts to study such relationship in adults of short-lived species (e.g. Brouwer et al 2007;Cohas et al 2009;Canal et al 2014; but see Olano-Marin et al 2011). However, the magnitude of HFCs in vital rates may vary according to population life history.…”
Section: Heterozygosity-survival Correlationmentioning
confidence: 99%
“…Nevertheless, no such evidence has been found in the few attempts to study such relationship in adults of short-lived species (e.g. Brouwer et al 2007;Cohas et al 2009;Canal et al 2014; but see Olano-Marin et al 2011). However, the magnitude of HFCs in vital rates may vary according to population life history.…”
Section: Heterozygosity-survival Correlationmentioning
confidence: 99%
“…Chapman et al. (2009) have suggested that the use of fitness‐correlated traits that are only weakly influenced by inbreeding may also hamper detection of HFCs, as might the varied demographic history of populations under study (see also Canal, Serrano, & Potti, 2014; Miller et al. 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Among adult marmots, however, no correlation between MLH and fitness was revealed (Cohas et al., 2009). Recent studies have further emphasized the importance of assessing multiple age classes in the detection and direction of HFCs (Annavi et al., 2014; Brommer et al., 2015; Canal et al., 2014; Monceau, Wattier, Dechaume‐Moncharmont, Dubreuil, & Cezilly, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Mojica and Kelly 2010). In studies investigating HFCs, fitness components are often considered separately with, for example, heterozygosity and shortterm survival (Bean et al 2004;Canal et al 2014) or heterozygosity and clutch size (Ortego et al 2007;Wetzel et al 2012). When more complex approaches are undertaken, the traits considered (heterozygosity and morphological traits such as body mass) typically act simultaneously on a single component of fitness such as survival (Richardson et al 2004).…”
Section: Introductionmentioning
confidence: 99%